Reference Values for Videofluoroscopic Measures of Swallowing: An Update - Steele, Catriona M; Bayley, Mark T; Bohn, Mary Kathryn; Higgins, Victoria; Peladeau-Pigeon, Melanie; Kulasingam, Vathany (Journal of speech, language, and hearing research, 2023)
It is essential that clinicians have evidence-based benchmarks to support accurate diagnosis and clinical decision making. Recent studies report poor reliability for diagnostic judgments and identifying mechanisms of impairment from videofluoroscopy (VFSS). Establishing VFSS reference values for healthy swallowing would help resolve such discrepancies. Steele et al. (2019) released preliminary reference data for quantitative VFSS measures in healthy adults aged < 60 years. Here, we extend that work to provide reference percentiles for VFSS measures across a larger age span. Data for 16 VFSS parameters were collected from 78 healthy adults aged 21-82 years (39 male). Participants swallowed three comfortable sips each of thin, slightly, mildly, moderately, and extremely thick barium (20% w/v). VFSS recordings were analyzed in duplicate by trained raters, blind to participant and task, using the Analysis of Swallowing Physiology: Events, Kinematics and Timing (ASPEKT) Method. Reference percentiles (p2.5, 5, 25, 50, 75, 95, and 97.5) were determined as per Clinical and Laboratory Standards Institute EP28-A3c guidelines. We present VFSS reference percentile tables, by consistency, for (a) timing parameters (swallow reaction time; the hyoid burst-to-upper esophageal sphincter (UES)-opening interval; UES opening duration; time-to-laryngeal vestibule closure (LVC); and LVC duration) and (b) anatomically scaled pixel-based measures of maximum UES diameter, pharyngeal area at maximum pharyngeal constriction and rest, residue (vallecular, pyriform, other pharyngeal locations, total), and hyoid kinematics (X, Y, XY coordinates of peak position; speed). Clinical decision limits are proposed to demarcate atypical values of potential clinical concern. These updated reference percentiles and proposed clinical decision limits are intended to support interpretation and reliability for VFSS assessment data. https://doi.org/10.23641/asha.24043041.